Management of Patients with Nonmetastatic Castration-Resistant Prostate Cancer: Recommendations of a Multidisciplinary Panel of Experts from South America. (9th November 2021) - Manneh, Ray; Brugés, Ricardo; Correa, Jose Jaime; Rojas, Julián; Rojas, Daniel; Villareal, Nicolás
Abstract : Most prostate cancer patients who undergo androgen-deprivation therapy or orchiectomy will eventually develop castration-resistant prostate cancer (CRPC), often preceded by a nonmetastatic CRPC state known as M0CRPC. The recent development of second-generation antiandrogens provides clinicians with efficacious and safe treatments for M0CRPC. However, the complexity of these patients, who typically have to deal with underlying comorbidities and polypharmacy, often challenges therapeutic decisions in this setting. The recent development of novel imaging techniques also provides clinicians with tools for detecting metastases with high sensitivity and specificity. However, the lack of evidence on the early detection of metastases and the corresponding impact on therapeutic decisions makes these techniques a double-edged sword that must be managed appropriately. Here, we present the expert view of the rapidly evolving concept of M0CRPC and provide recommendations for the identification of these patients, the appropriate use of the emerging imaging modalities, and patients' management, particularly considering their clinical complexity and the recent development of next-generation antiandrogens.